Economical aspects of the improvement of a mechanical vapour compression desalination plant by dropwise condensation - Lukic, Nebojsa; Diezel, Liv; Fröba, Andreas Paul; Leipertz, Alfred (Desalination, 2010)
By applying ion implantation on metallic surfaces for the adjustment of dropwise condensation (DWC), the condensation heat transfer coefficient can be significantly improved. Using this thermal desalination process, mechanical vapour compression (MVC) in particular can be more effective. In comparison with common condensation processes, where filmwise condensation (FWC) dominates, the main heat exchanger area and/or the minimum temperature difference between the evaporation-condensation sides can be reduced. Within the present study, three scenarios regarding the economical effects of improving the condensation heat transfer process are discussed. Based on models of the heat transfer and product water costs, a reduction by as much as 35.4% could be demonstrated. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Desalination; Mechanical vapour compression; Dropwise condensation; Plate heat exchanger; Economical aspects